2014
DOI: 10.1039/c4ra10408k
|View full text |Cite
|
Sign up to set email alerts
|

A multiple-assembly/one-pot-crystallization strategy for a relatively more eco-friendly synthesis of hydrothermally stable mesoporous aluminosilicates

Abstract: Mesoporous aluminosilicates (MA) with high hydrothermal stability obtained by assembly of zeolite Y precursors are attractive for the potential application in heavy oil catalytic cracking. A relatively more eco-friendly synthesis of MA with low synthesis cost and waste water discharge is particularly appealing. We report on the green synthesis of MA via a multiple-assembly/one-pot-crystallization (MA/OC) process by recycling the non-reacted reagents in the assembly mother liquor after separating the assembly s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…Mother liquor recycling (MLR) procedures have been performed for preparation of various microporous zeolites, such as Y, ZSM-5, and TS-1 . On the basis of the above study, our group reported the application of MLR in the preparation of MAs with significantly decreased amounts of organic surfactants and water . However, MLR mentioned above is a relatively complicated procedure, and in some cases the process is difficult to control.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mother liquor recycling (MLR) procedures have been performed for preparation of various microporous zeolites, such as Y, ZSM-5, and TS-1 . On the basis of the above study, our group reported the application of MLR in the preparation of MAs with significantly decreased amounts of organic surfactants and water . However, MLR mentioned above is a relatively complicated procedure, and in some cases the process is difficult to control.…”
Section: Introductionmentioning
confidence: 99%
“…11 On the basis of the above study, our group reported the application of MLR in the preparation of MAs with significantly decreased amounts of organic surfactants and water. 12 However, MLR mentioned above is a relatively complicated procedure, and in some cases the process is difficult to control. Another disadvantage of MLR is that the accumulation of inorganic salts will decrease the cloud point of P123.…”
Section: Introductionmentioning
confidence: 99%
“…A series of mesoporous aluminosilicates (MAs) with good hydrothermal stability have been prepared by self-assembly of basic characteristic structure units of microporous zeolite Y by our group. Much attention has been focused on these materials obtained by this novel strategy because of their distinct textural structures and their potential application in heavy oil catalytic cracking . As we know, active micelles are prerequisite for the assembly of aluminosilicate raw materials. , On the other hand, active micelles will exist only in low concentration of P123 solution, leading to the low utilization efficiency of both organic template and water .…”
Section: Introductionmentioning
confidence: 99%
“…For example, 0.5 g of crystal seeds is required for per gram of MAs product . For mother liquor recycling (MLR) by assembly and crystallization in high precursors concentration, although decreased amounts of organic surfactants and water are achieved, the ordering of final products is unsatisfactory due to the decrease of the cloud point of P123. In addition, MLR mentioned above is a complicated process, and the repeatability of this procedure is relatively poor. Consequently, it is still a big challenge to develop a feasible and effective route to improve the utilization efficiency of P123 in obtaining MAs.…”
Section: Introductionmentioning
confidence: 99%